PLURALITY OF RELIGION IN CHRISTIAN VIEWS AND THE IMPLICATIONS FOR CHRISTIAN RELIGIOUS EDUCATION - Bahabol, Edim (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2019)
This article aims to describe the plurality of religions in the Christian view and how they are implicated in Christian Religious Education. The method used is quantitative description, where the authors collect material from various sources of writing that relate to religious plurality and Christian views view it. The result of this writing is the discovery of the first theocentric approach, namely religions that exist in a shared environment and life that all come from one common root or ancestor, and from the same God. Second, christocentric, which prioritizes the discussion of the relationship of Christianity with plurality or other religions by highlighting Jesus as a measure. The implication is first the curriculum and specifically the material or teaching material needs to be adapted to the context. Second, the speakers as resource persons, whoever they are, who are involved in the teaching of PAK, need to have at least adequate knowledge, insights and skills about the condition of plural religious communities and pluralism into general principles and characters.